Three dimensional surface patterning atop poly(methyl Methacrylate) (PMMA) - Zhao, Yong (2013)
We demonstrate a novel approach to fabricate three dimensional (3-D) surface patterns atop poly(methyl methacrylate) (PMMA). This approach utilizes both shape recovery behavior and swelling phenomenon of the PMMA. The simplicity in the fabrication process affirms the low-cost nature of this approach. Moreover, as obtained 3-D patterned PMMA sample can be used as artificial compound eye.